2004
DOI: 10.1055/s-2004-823124
|View full text |Cite
|
Sign up to set email alerts
|

Donor Nerve Selection in Facial Reanimation Surgery

Abstract: The motor components of local cranial nerves provide a series of options for the surgical rehabilitation of the paralyzed face. Nerve donor sites vary with respect to their motor power, functional deficit, and synergy with facial expression. A thorough understanding of each donor nerve's strengths and weaknesses facilitates the selection process. Technical modifications to reduce donor site morbidity and the emerging role of the masseter nerve are examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…46 Comparing the commonly used nerve-to-masseter and cross-facial nerve graft, the authors agree that the nerveto-masseter provides more excursion, a shorter convalescence time, but less spontaneity and the need for more intensive smile training, whereas the cross-facial nerve graft delivers spontaneous emotions and resting tone but less excursion and demands more recovery time. [47][48][49][50][51] Nevertheless, some studies suggest that spontaneity can also be achieved by a nonfacial donor source. [52][53][54] The deep temporal branch of the trigeminal nerve supplying the temporalis muscle has been described as nonfacial donor source for the reanimation of the forehead by Dauwe et al 7 They found 1496 axons at the level of the zygomatic arch and 534 axons at a distance of 3 cm for the temporal branch middle division.…”
Section: Discussionmentioning
confidence: 99%
“…46 Comparing the commonly used nerve-to-masseter and cross-facial nerve graft, the authors agree that the nerveto-masseter provides more excursion, a shorter convalescence time, but less spontaneity and the need for more intensive smile training, whereas the cross-facial nerve graft delivers spontaneous emotions and resting tone but less excursion and demands more recovery time. [47][48][49][50][51] Nevertheless, some studies suggest that spontaneity can also be achieved by a nonfacial donor source. [52][53][54] The deep temporal branch of the trigeminal nerve supplying the temporalis muscle has been described as nonfacial donor source for the reanimation of the forehead by Dauwe et al 7 They found 1496 axons at the level of the zygomatic arch and 534 axons at a distance of 3 cm for the temporal branch middle division.…”
Section: Discussionmentioning
confidence: 99%
“…13 Complete sectioning of the spinal accessory nerve can produce significant shoulder weakness, and the transfer lacks the ''physiologic dynamism'' other cranial nerves provide. 14…”
Section: Other Available Optionsmentioning
confidence: 99%
“…However, this option is inferior for minimizing morbidity concerning shoulder weakness. 14 In the clinical scenario of soft tissue loss, options for reconstruction expand to incorporating a vascularized nerve graft with a free anterolateral thigh flap. 17 Vascularized nerve grafts have several benefits when compared to their non-vascularized counterparts, including an increase in the number of myelin fibres, thickness, axon diameter, faster axonal regeneration and higher axonal count.…”
Section: Other Available Optionsmentioning
confidence: 99%
“…Der Patient kann auch ein "Masseter-Lachen" erlernen, indem er den M. masseter anspannt, ohne eine Kaubewegung mit den Backenzähnen durchzuführen. Zudem soll es möglich sein, durch kortikale Adaptation in der Großhirnrinde ein spontanes Lächeln zu entwickeln[28][29][30][31][32]. Es handelt sich um einen kräftigen Nerv.▪Die Auslenkung des Mundwinkels ist deutlich.…”
unclassified